2017
DOI: 10.1108/jsbed-07-2016-0117
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial mindset and the role of universities as strategic drivers of entrepreneurship

Abstract: Purpose The purpose of this paper is to provide insight into the factors that influence the mindset of youth in the United Arab Emirates (UAE) in choosing entrepreneurship as their future employment. It also suggests the pathway to improve the role of the universities as strategic drivers in inducing an entrepreneurial mindset. Design/methodology/approach An exhaustive literature review of extant research followed by an exploratory study was conducted. Furthermore, to understand factors influencing the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
1
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 86 publications
11
72
1
12
Order By: Relevance
“…The significance of entrepreneurship education and university environment has been acknowledged as one of the crucial factors that help youths to understand and foster an entrepreneurial interest and attitude (Gorman et al, 1997;Kourilsky and Walstad, 1998;Wang and Wong, 2004;Jabeen et al, 2017). Entrepreneurship education at the university level provides the opportunity for students to be more aware of the latest developments, which allows them to have a more clear vision on how they can implement these developments into future business.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of entrepreneurship education and university environment has been acknowledged as one of the crucial factors that help youths to understand and foster an entrepreneurial interest and attitude (Gorman et al, 1997;Kourilsky and Walstad, 1998;Wang and Wong, 2004;Jabeen et al, 2017). Entrepreneurship education at the university level provides the opportunity for students to be more aware of the latest developments, which allows them to have a more clear vision on how they can implement these developments into future business.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…Recent studies such as Durst and Sedenka (2016) in Sweden, Jabeen et al (2017) in United Arab Emirates, Shahid et al (2017) in Pakistan and Hasan et al (2017) in Bangladesh among others suggested that university environment where students learn plays a pivotal role in encouraging students to develop business ideas and start up their own business. This seems to help students mitigate any adverse impact that their negative perceptions that surrounds them might have on their entrepreneurial intentions (Shahid et el., 2017).…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…With regards to this [12,13] suggested the need for new school curriculum that would adopt the teaching of entrepreneurial education, this will serve as a solution to the current issues of unemployment and high poverty rate. According to Ghina, Simatupang, and Gustomo, [14]the intention of instilling entrepreneurial mindset into students is to produce novice educated entrepreneurs as well as innovative ventures that can form jobs opportunities.. [15] observed based on their research, the need for encouragement both from the government and the business community to invest heavily in EET more especially at the early age. They also reiterated that instilling entrepreneurial mindset among teaming youth would influence global economic development positively In view of this [16] conducted a research on the Japanese high school students and found that to influence students entrepreneurial mindset there should be an innovation and convert the ideas to reality is one of the vital role of EET.…”
Section: The Need For Integrating Eet In Technical Collegesmentioning
confidence: 99%
“…(Etkowitz et al, 2000). Cabe ressaltar que o ensino empreendedor e a sua relação com a maior propensão a empreender ainda possui resultados difusos e é tema de acalorados debates (Chen, Hsiao, Chang, Chou, Chen & Shen, 2013;Premand, Brodmann, Almeida, Grun & Barouni, 2016;Habibov et al, 2016;Jabeen, Faisal & Katsioloudes, 2017). Ao mesmo tempo, parece haver certo consenso de que as práticas de ensino de empreendedorismo são ultrapassadas, confusas e carecem de base teórica consistente (Gibb, 2002;Anderson & Ronteau, 2017).…”
Section: Instituiçõesunclassified